(untitled) (Circe de clásicos y modernos, 2018)
In this paper, we offer the translation from latin to spanish of Giovanni Pico della Mirandola’s letter to his friend Andrea Corneo from Urbino with introduction and notes. In this text, Pico presents his points of view about one of the most important problems along the fifteenth century: the choice between active and contemplative life. In addition, the letter enter upon the so-called “incident of Arezzo”, a confus-ing episode in which the young count kidnapped Giuliano Mariotto de’ Medici’s wife. Along the text, Pico reveals himself as classical latin authors’s imitator, among others, Seneca, Horace, Gellius, Plautus, Terence and specially Cicero.